Palladium Catalysts with Sulfonate-Functionalized-Nhc Ligands for Suzuki-Miyaura Cross-Coupling Reactions in Water - Godoy-Gonzalez, F; Godoy-Gonzalez, F (2011)
Four new Pd(II) complexes containing sulfonate-functionalized N-heterocyclic carbene ligands have been synthesized. All new complexes are palladium bis-NHCs, in which the ligands adopt a monodentate, bis-chelating, and pincer coordination form, so that a good comparison between their catalytic activities can be performed. The complexes have been used in the Suzuki-Miyaura cross-coupling reaction between aryl halides and phenylboronic acid in water and in iPrOH/water. The bis-NHC-palladium complex 1, in which the two NHC ligands are in a relative cis configuration, affords the best catalytic outcomes, with high TON values of 105 for 4-bromoacetophenone and 3.7 - 104 for 4-chloroacetophenone. © 2011 American Chemical Society.